RETRACTED: Isolation of active metabolites of B. ginsengihumi M2.11 with fungicidal activity - Itkina Daria; Sharipova Margarita (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001